PROSES BERPIKIR SISWA YANG MENGALAMI MATH-ANXIETY DALAM MENYELESAIKAN MASALAH SISTEM PERSAMAAN LINIER DUA VARIABEL - Muhammad Irfan (KALAMATIKA Jurnal Pendidikan Matematika, 2018)
Algebra is one of the most difficult material for students to understand, especially those experiencing math-anxiety. This study aimed to describe: (1) the thinking process of students who have high math-anxiety in solving mathematical problems according to Polya steps, (2) the thinking process of students who have low math-anxiety in solving mathematical problems according to Polya steps. Type this research is qualitative research with case study method. Sampling is done by purposive sampling technique. Subjects used in this study as much as two research subjects, namely: students who have high anxiety math, students who have low anxiety math. The instruments used to collect data are classification of anxiety level of mathematics learning, mathematics problem sheet, and interview guidance. The data validation test used is the triangulation test of time. In this study, researchers used a type of reflective and creative thinking to analyze the thinking process of the subject. The results show: (1) when understanding the problem, planning problem solving, running problem-solving plan, and re-examining answers, students experiencing high math-anxiety using reflective thinking process, (2) when understanding the problem and re-examining answers, students who experience low anxiety math using reflective thinking processes, while at the time of planning problem solving and running problem-solving plans, the subject engages in a process of reflective and creative thinking.